Application of Dosage Combinations of Evagrow Biofertilizer and Chemical Fertilizer on Soil Characteristics, Growth and Yield of Rice - Merit, I Nyoman; Narka, I Wayan; Kusmawati, Tatiek (Advances in Tropical Biodiversity and Environmental Sciences, 2017)
Research on the effect of dosage combination of Evagrow bio-fertilizer and chemical fertilizers on soil properties, growth and yield of rice has been carried out in the glasshouse, Faculty of Agriculture, Udayana University using factorial experiment with a Randomized Block Design (RBD). The first factor is Evagrow bio-fertilizer in 3 level, i.e. E0 (without bio-fertilizers), E1 (5 g bio-fertilizer/L) E2 (10 grams bio-fertilizer/L). The second factor is chemical fertilizer, which consists of 3 levels: K0 (without chemical fertilizers), K1 (150 kg Urea/ha + 75 kg SP36/ha + 37.5 kg KCl/ha), K2 (300 kg Urea/ha + 150 kg SP36/ha + 75 kg KCl/ha). The results showed that chemical fertilizers give a significant and very significant effect on most of the rice growth and yield parameters. The application of chemical fertilizers K1 and K2 increased yield of dry grain harvest to 52.87% and 102.54% compared to controls.  Application of Evagrow bio-fertilizer did not significantly increase growth and yield of rice. There is no interaction between chemical fertilizers and Evagrow bio- fertilizer.  Similarly to some of the soil characteristics, biological fertilizer and chemical fertilizer application did not show significant effect on most of the soil characteristics, except on salt levels. Keywords : Evagrow Biofertilizer, Inorganic Fertilizer, Oryza Sativa